Analisis Penggunaan Wordwall Sebagai Peran Teknologi Dalam Pembelajaran di Sekolah Dasar - Yasa, Puspita; T, Trimurtini (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Rapid advances in technology and information can encourage progress in the field of education. Access to information and communication is now increasingly easier, especially in the field of education. The development and facilitation of the learning process requires the application of learning innovation so that teachers must train their creativity in order to utilize technology as a tool that will encourage the achievement of learning goals. To arouse students' interest and make learning fun, teachers can take advantage of advances in information and technology by using Wordwall, an online educational game. Wordwall is an interactive educational game that is great for encouraging interesting learning because it has various game aspects that, through gamification, help students absorb the material more easily. Using a library approach as a source of knowledge about innovative learning technology throughout the implementation of distance learning. This research technique used a qualitative approach. To identify and characterize various learning innovations implemented by teachers, this research used descriptive data analysis methodology. Wordwall media included multiple choice questions with matching answer pairs, categorizing, anagrams, word searches, random words, and matching among other quiz-style games. It can be seen from the activity and improvement in understanding that the Wordwall application was suitable for elementary school children. Teachers were able to innovate in conducting learning through the Wordwall website media.